2022
DOI: 10.5173/ceju.2022.0175
|View full text |Cite
|
Sign up to set email alerts
|

Visceral adiposity index in kidney stone patients who have undergone surgery

Abstract: Introduction The visceral adiposity index (VAI) is a gender-specific metabolic index that indirectly measures visceral adipose function and distribution using waist circumference, body mass index (BMI), and triglyceride and high-density lipoprotein (HDL) cholesterol values. To assess visceral fat in the diagnostic pathway of urinary stone patients, we investigated the relationship between the VAI and nephrolithiasis as well as the relationship between the VAI and stone and surgery-related paramete… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 24 publications
0
2
0
Order By: Relevance
“…Recently, a retrospective study reported by Sönmez et al. ( 33 ) concluded that the VAI was positively correlated with the creatinine levels in patients with KS. However, evidence regarding the association between the VAI and KS are limited.…”
Section: Discussionmentioning
confidence: 97%
“…Recently, a retrospective study reported by Sönmez et al. ( 33 ) concluded that the VAI was positively correlated with the creatinine levels in patients with KS. However, evidence regarding the association between the VAI and KS are limited.…”
Section: Discussionmentioning
confidence: 97%
“…A US study found a 3% prevalence of kidney stones in participants without comorbid metabolic syndrome and a significant increase in the prevalence of kidney stones in participants with comorbid metabolic syndrome (hyperlipidemia, hypertriglyceridemia, hyperglycemia, hypertension, and abdominal obesity), with a 9.8% prevalence of kidney stones in those with five comorbid metabolic syndrome features [ 35 ]. Significant dyslipidemia has been identified in patients with kidney stones [ 36 ]. Another study found that dyslipidemia was associated with altered chemical composition in the urine and this chemical composition played a key role in stone formation, such as patients with high triglycerides exhibited increased uric acid excretion and significantly lower urinary pH, those with high total cholesterol had significantly higher urinary calcium levels, and patients with reduced high-density lipoprotein (HDL) showed significantly higher levels of oxalic acid and uric acid in their urine [ 37 ].…”
Section: Discussionmentioning
confidence: 99%